2020
DOI: 10.1177/0886260520912585
|View full text |Cite
|
Sign up to set email alerts
|

Physical Abuse of Children by Stepfathers in Colombia

Abstract: Evolutionary psychologists claim that stepparents perpetrate substantially more child physical abuse than genetic parents, and that they do so because they are less invested in genetically unrelated children. The objective of this study was to examine these claims by investigating whether, and why, fathers in a Colombian sample physically abused their stepchildren more than their genetic children. Fathers ( N = 86) and their partners living in Bogotá were interviewed by Klevens et al. Half of the fathers had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
(170 reference statements)
1
9
0
Order By: Relevance
“…Because of limitations of the dataset, in this study we included only one—father’s age—and found that this alone accounted for much of the overrepresentation of stepfathers among the perpetrators. But there are many other possible confounds that are likely to explain still more—and perhaps all—of stepfathers’ apparent increased risk to children (Berger et al, 2009; Giles-Sims & Finkelhor, 1984; Malvaso et al, 2015; Nobes et al, 2018; Temrin et al, 2011). For example, Nobes et al (2018) reported in their analysis of Colombian data that factors such as parents’ conflict, histories of abuse, and father’s stress all accounted for considerably more of the variance of child physical abuse than did father’s age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of limitations of the dataset, in this study we included only one—father’s age—and found that this alone accounted for much of the overrepresentation of stepfathers among the perpetrators. But there are many other possible confounds that are likely to explain still more—and perhaps all—of stepfathers’ apparent increased risk to children (Berger et al, 2009; Giles-Sims & Finkelhor, 1984; Malvaso et al, 2015; Nobes et al, 2018; Temrin et al, 2011). For example, Nobes et al (2018) reported in their analysis of Colombian data that factors such as parents’ conflict, histories of abuse, and father’s stress all accounted for considerably more of the variance of child physical abuse than did father’s age.…”
Section: Discussionmentioning
confidence: 99%
“…When, like Daly and Wilson (1994), we considered only young children, the risk from stepfathers was about six times the risk from genetic fathers. But even this figure is likely to be a substantial overestimate because stepparents are defined and reported very differently in the Homicide Index and the population data, and because there are likely to be many other confounding variables (Berger et al, 2009; Giles-Sims & Finkelhor, 1984; Malvaso et al, 2015; Nobes et al, 2018; Temrin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they have not adequately tested or addressed the extent to which the Cinderella effect is accounted for by confounding factors (see the section “Confounding Factors”). Daly (2022) provides many examples of the approach that he and his colleagues have often taken regarding this issue: he does not acknowledge the implications of Nobes et al’s (2019) finding that father’s age is a strong confounding factor; he rejects the possibility of a socioeconomic confound on the basis of only two studies; when referring to studies such as Bachrach (1983) and Scott (1973) he reports only the findings that support the evolutionary account—in particular, that stepfathers are overrepresented, and that incomes in the two family types are similar—while saying nothing about other characteristics of stepfamilies and filicidal fathers, reported in the same studies, that are likely to be confounding variables; and he omits to mention any of the recent research (e.g., Berger et al, 2009; Malvaso et al, 2015; Nobes et al, 2019, 2022; Temrin et al, 2011; Turner et al, 2007) that shows that controlling for factors such as mental health, chronic stress, alcoholism, antisociality, history of abuse, and family resources substantially attenuates the increased risk to stepchildren.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these results are consistent with those of a longitudinal study conducted by Luntz and Widom, who suggested that individuals who experience abuse/neglect in childhood have a higher prevalence of ASPD (Luntz & Widom, 1994). In addition, parents with ASPD may play an important role in the development of abused individuals into ASPD, Delisi and his colleague found that parents with ASPD were more likely to abuse their children sexually, physically and emotionally (DeLisi et al, 2019;Lobbestael et al, 2005), and some parents may have experienced maltreatment or violent tendencies during the childhood, this intergenerational transmission of violence has an impact on shaping children's values, and long-term maltreatment by parents could predict individuals' antisocial behavior to some extent (Milner et al, 2010), but timely intervention and good social support can break this cycle (Forster et al, 2020;Nobes et al, 2020). Considering that the proportion and degree of childhood maltreatment of ASPD population in this study are more prominent, it may be a worthy research topic to further collect parents' data of ASPD population in the next study.…”
Section: Discussionmentioning
confidence: 99%